PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN EFIKASI DIRI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR GURU SMK NEGERI DI KABUPATEN BEKASI - Herry Nugroho (Jurnal Manajemen Pendidikan, 2017)
the objective of this research is to obtain information concerning to the effect of transformational leadership and self efficacy toward teachers organizational citizenship behavior in state vocational school in Bekasi district.The research was conduct by using survey method with path analysis in testing hyphotesis. In this research, 165 from 280teacher of teachers selected random sampling. The research was focused on three aspect; transformational leadership and self efficacy toward teachers OCB.The data were collected with questionnaire and analyzed with path analysis. Result on the analysis it is conculaded that (1) there the positive direct effect of transformational leadership toward OCB, (2) there is positive direct effect of self efficacy toward OCB and (3) there is positive direct effect of transformational leadership toward self efficacy.